Feasibility Analysis of Primary Drainage Capacity on Jalan Dr. M. Hatta - Lucyana; eka rizki meiwinda; Azwar Azwar; liwon Saputra; Ali Mas'ud Dwi Cahyono (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2026)
Drainage is a facility and infrastructure for channeling rainwater from one place to another. The aim of this research is to calculate the drainage capacity of the primary channel on Jalan Dr. M. Hatta, East Baturaja District. The method used is descriptive with a qualitative approach. The research location is on Jalan Dr. M. Hatta, East Baturaja District to provide input and recommendations for the implementation of the drainage system on Jalan Dr. M. Hatta  After re-planning the drainage dimensions of the primary channel on Jalan Dr M. Hatta, the channel that has been re-planned is able to carry the planned discharge because Q channel > Q planned. as a result of the channel dimensions being inadequate to channel the flood discharge that occurs. Therefore, re-planning of the channel dimensions is necessary. The proposed design indicates variations in channel width and depth, with T ranging from 3 to 4 m, B from 2.0 to 3.5 m, and h from 1.4 to 1.6 m along Sta. 1–6.